2021
DOI: 10.12688/openreseurope.13231.2
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the trust of nurses to advance a digital agenda in Europe: a critical review of health policy literature

Abstract: This article is a critical and integrative review of health policy literature examining artificial intelligence (AI) and its implications for healthcare systems and the frontline nursing workforce. A key focus is on co-creation as essential for the deployment and adoption of AI. Our review hinges on the European Commission’s White Paper on Artificial Intelligence from 2020, which provides a useful roadmap. The value of health data spaces and electronic health records (EHRs) is considered; and the role of advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This study also found that the competencies of the important phases of the nursing process, nursing diagnoses, interventions, and outcomes were at a low level. Concerns must be raised, since structured and high-quality nursing data are a basis for utilizing big data in nursing and quality management, 13,21,28 affecting the reliability of results produced by artificial intelligence software, such as problem-solving software programs, to provide support to nurses and help them make more informed decisions in patient care 29 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also found that the competencies of the important phases of the nursing process, nursing diagnoses, interventions, and outcomes were at a low level. Concerns must be raised, since structured and high-quality nursing data are a basis for utilizing big data in nursing and quality management, 13,21,28 affecting the reliability of results produced by artificial intelligence software, such as problem-solving software programs, to provide support to nurses and help them make more informed decisions in patient care 29 …”
Section: Discussionmentioning
confidence: 99%
“…Concerns must be raised, since structured and high-quality nursing data are a basis for utilizing big data in nursing and quality management, 13,21,28 affecting the reliability of results produced by artificial intelligence software, such as problem-solving software programs, to provide support to nurses and help them make more informed decisions in patient care. 29 Inadequate training, lacking connections with daily work processes, has been presented to associate with the lack of digital skills. 33 According to nurses, the best way to learn is learning by doing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific rules are missing in the form of protocols as data sharing means, compliant with data governance and protection regulations, to provide the citizens the ability to receive a copy of their own data and control them. In this manuscript, the InteropEHRate [8] project and its main results are presented, for releasing locally siloed health data and providing citizens' control into managing their personal health data among multiple countries and healthcare providers, through mature data exchange protocols.…”
Section: Introductionmentioning
confidence: 99%